Purpose as a Sign of the Subjective Side of Corpus Delicti Provided By Article 174.1 of the Criminal Code of the Russian Federation - M. V. Lupyr' (Сибирское юридическое обозрение)
The Author of the article considers the problematic issues of the subjective side of the corpus delicti of the legalization (laundering) of money or other property acquired by a person as a result of his committing a crime under Art. 174.1 of the Criminal Code of the Russian Federation. Focusing on the objectives of the composition, the Author, in terms of civil law, considers the legal possibility of imparting a lawful type of possession, use and disposal of money or other property acquired by criminal way, using the methods specified in the Resolution of the Plenum of the Supreme Court of July 7, 2015 №. 32 “On judicial practice in cases of legalization (laundering) of money or other property acquired by criminal way, and on the acquisition or sale of property knowingly obtained by criminal way”. Having considered the value of the powers of possession, use and disposal, the Author comes to the conclusion that legalization (laundering) is possible only through the implementation of such actions, as a result of which evidence will be created justifying the legal nature of the origin and possession of the property acquired by criminal way, equated with the presence of the guilty right of ownership.